Perfil de puesto por competencias y su impacto en el proceso de selección y desempeño laboral de los colaboradores del Sistema de Administración Tributaria de Lima – SAT - Mejia Muñoz, Lady Grecia Rossemary (2019)
it is intended to demonstrate how the implementation of a new advanced practice in the field of human resources as the management model of people by competences, can be a factor that enhances the capabilities of employees, in the framework of an effective and efficient management of human resources as part-of the National Public Management Modernization Policy. The competency model that is developed in the research is the best practice to make the selection of people and their subsequent performance evaluation. The importance of this practice is based as an effective tool to attract and select better people, as a methodology to forge human capital in the medium and long term; as well as a way to ensure that the organization’s investment in its staff will achieve the expected results.